1995
DOI: 10.1063/1.358704
|View full text |Cite
|
Sign up to set email alerts
|

Optical second-harmonic generation as a probe of the temperature dependence of the distribution of sites in a poly(methyl methacrylate) polymer doped with disperse red 1 azo dye

Abstract: We have applied electric-field-induced optical second-harmonic generation to measure the distribution of chromophore sites in a dye-doped polymer [disperse red 1 in poly (methyl methacrylate)] in terms of the standard α and β parameter, that is, the decay rate and the breadth parameter. These parameters have been measured from 100 to 430 K and are modeled with a smooth function over that temperature range. Over a narrow region of temperature where second-harmonic data from other groups exist, we find that our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…The KWW function has been extensively used to model the relaxation of azo molecules in amorphous polymers from dielectric and second harmonic generation measurements, [43][44][45][46] to investigate the dynamics of photoinduced isomerization of azobenzene moieties in liquid-crystalline polymers from forced Rayleigh scattering measurements, 47 and to study the dynamics of copolymers containing two types (one polar and another one less polar) of azobenzene side chains from birefringence measurements. 48 The relaxation curves were thus fitted by the function where y is either T 0 , T 2 , or P 2 , A is the residual orientation after relaxation, A + B is the induced orientation just before the laser beam is turned off (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The KWW function has been extensively used to model the relaxation of azo molecules in amorphous polymers from dielectric and second harmonic generation measurements, [43][44][45][46] to investigate the dynamics of photoinduced isomerization of azobenzene moieties in liquid-crystalline polymers from forced Rayleigh scattering measurements, 47 and to study the dynamics of copolymers containing two types (one polar and another one less polar) of azobenzene side chains from birefringence measurements. 48 The relaxation curves were thus fitted by the function where y is either T 0 , T 2 , or P 2 , A is the residual orientation after relaxation, A + B is the induced orientation just before the laser beam is turned off (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…To compare the orientation and relaxation dynamics in various samples, an average rate constant 〈k〉 can be defined as [43][44][45][46] where Γ is the gamma function.…”
Section: Methodsmentioning
confidence: 99%
“…[14] This model assumed a dilute collection of non-interacting molecules that rotate freely above the glass transition temperature of the polymer, an assumption that was found to be consistent with experimental evidence. [15,16] At high concentrations, the thermodynamic model for poling predicted exceptionally large electro-optic coefficients that greatly exceeded the performance of lithium niobate. Harper and coworkers showed that this model overestimated the bulk response because it did not account for chromophore-chromophore electrostatic interactions that become dominant at high concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that polymers are microscopically inhomogeneous leading to a distribution of sites so that each molecule that is embedded in a polymer sees a different local environment. 13,14 In contrast to a liquid, where broadening of the energy levels are due to stochastic collisional processes, in a polymer, broadening can be dominated by a distribution in local fields due to the distribution sites.…”
mentioning
confidence: 99%